LEGAL PROTECTION OF THE RIGHTS OF REFUND OF CONCURRENT CREDITORS IN THE BANKRUPTCY CASE OF PT. BANGUN INVESTA GRAHA (DEBTOR) IS CONNECTED WITH LAW NUMBER 37 OF 2004 CONCERNING BANKRUPTCY AND DELAY OF DEBT PAYMENT OBLIGATIONS. (Decision Study: Number 879 K/Pdt.Sus-Pailit/2020) - Wike Nopianti; Deny Guntara; Muhamad Abas; Adyan Lubis (Jurnal Ilmiah Advokasi, 2023)
Law 37 of 2004 states that the debt to the creditor PT has been determined. Bangun Investa Graha can be billed on time, but PT. PPJB is terminated unilaterally and in bad faith by Bangun Investa Graha, which frequently ignores calls from creditors. In accordance with normative legal principles, this study employs qualitative research methods. In this approach, the author employs a normative juridical strategy. It is possible to draw the conclusion based on the findings of the research that has been discussed that Law Number 37 of 2004 Concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU) does not have any legal function against concurrent creditors who are not guaranteed. When a debtor has debts that are greater than his assets, the responsibilities of the debtor and his directors are not taken into account in the Panel of Judges' decision in this case. Due to the fact that the debtor's assets will not be distributed appropriately if the debtor is declared bankrupt by the court, concurrent creditors will suffer greater losses. The Panel of Judges considered the decision in Renvoi's cassation without understanding why the cassation was rejected—whether the debtor's condition was insufficient to pay creditors or the debtor did not want to pay concurrent creditors.Keywords: Debts, Debtors, Creditors, Losses